Maternal and Fetal Outcomes After Interferon Exposure During Pregnancy: A Systematic Review With Meta-Analysis - Zhang, Mengmeng; Fu, Shan; Ren, Danfeng; Wu, Yuchao; Yao, Naijuan; Ni, Tianzhi; Feng, YaLi; Chen, Yaolong; Chen, Tianyan; Zhao, Yingren; Liu, Jinfeng (Frontiers in Reproductive Health, 2021)
Interferon (IFN) is widely applied in viral hepatitis and multiple myeloproliferative diseases. Whereas, there is considerable controversy on how to deal with unintended pregnancy during IFN treatment, even selective termination is suggested by hepatologists. To settle this clinical dilemma, we conducted a systematic review to retrieve all published articles involving IFN exposure during pregnancy up until March 31 2021. Only 8 case reports were retrieved relevant with outcomes of pregnant women with viral hepatitis exposed to IFN-α, 17 studies reporting pregnancy outcomes after type I IFNs exposure involving 3543 pregnancies were eligible for meta-analysis. None birth defect was reported in the case reports of pregnant women with viral hepatitis. The meta-analysis showed that risks of pregnancy outcomes, as well as birth defects were not increased after IFN-α exposure. Further comprehensive meta-analysis concerning with IFN-α and IFN-β exposure demonstrated the risks of live birth (OR 0.89, 95%CI: 0.62-1.27), spontaneous abortion (OR 1.09, 95%CI: 0.73-1.63), stillbirth (OR 1.38, 95%CI: 0.51-3.72), preterm delivery (OR 1.24, 95%CI: 0.85-1.81), and maternal complications (OR 0.72, 95%CI: 0.38-1.38) were not increased in patients exposed to IFN. The pooled estimates of live birth, spontaneous abortion, stillbirth, preterm delivery, and maternal complications were 85.2%, 9.4%, 0%, 7.5%, and 6.5%, respectively. Importantly, the risk of birth defects was not increased (OR 0.68, 95%CI: 0.39-1.20) after IFN exposure, with a pooled rate of 0.51%. Therefore, IFN exposure does not increase the prevalence of spontaneous abortion, stillbirth, preterm delivery, and birth defects. Clinical decision should be made after weighing up all the evidence.